2017
DOI: 10.3892/mco.2017.1293
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA HOTTIP is able to predict poor prognosis in various neoplasms: A meta‑analysis

Abstract: Abstract. HOXA distal transcript antisense RNA (HOTTIP), a critical oncogenic long non-coding RNA, has been reported to be aberrantly regulated in various cancer types. The present meta-analysis aimed to investigate HOTTIP as a potential clinical applicable prognostic biomarker in malignant neoplasms. Literature collections were performed by searching the electronic databases, PubMed and Web of Science (up to July 20, 2016). All the relevant searches were conducted to identify the association of HOTTIP with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The contribution of HOTTIP as having oncogenic roles has been revealed in tumorigenesis; recent advances have confirmed that HOTTIP is frequently overexpressed in many tumors to play oncogenic roles in cancer development and progression, including HCC [31]. HOTTIP expression was noticed to increase the HCC cell proliferation [48] and was associated with HCC progression and poor clinical outcome [31,49]. The diagnostic performance of HOTAIR and HOTTIP gene expressions as markers in cirrhotic patients at different cut-off points using ROC curve showed that no significant difference between cirrhotic and noncirrhotic patients regarding HOTAIR at the cut-off value of 4.7, with sensitivity of 48.0% and specificity of 72.0% with areas under curve (AUC) of 52.0 (p value = 0.8, 95% confidence interval C.I 35.6%-68.4%) and accuracy of 60.0%, also no significant difference between cirrhotic and non-cirrhotic patients regarding HOTTIP at the cut-off value of 13.4, with sensitivity of 32.0% and specificity of 100.0% with areas under curve (AUC) of 53.9 (p value = 0.640, 95% confidence interval C.I 37.1%-70.8%) and accuracy of 66.0%.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of HOTTIP as having oncogenic roles has been revealed in tumorigenesis; recent advances have confirmed that HOTTIP is frequently overexpressed in many tumors to play oncogenic roles in cancer development and progression, including HCC [31]. HOTTIP expression was noticed to increase the HCC cell proliferation [48] and was associated with HCC progression and poor clinical outcome [31,49]. The diagnostic performance of HOTAIR and HOTTIP gene expressions as markers in cirrhotic patients at different cut-off points using ROC curve showed that no significant difference between cirrhotic and noncirrhotic patients regarding HOTAIR at the cut-off value of 4.7, with sensitivity of 48.0% and specificity of 72.0% with areas under curve (AUC) of 52.0 (p value = 0.8, 95% confidence interval C.I 35.6%-68.4%) and accuracy of 60.0%, also no significant difference between cirrhotic and non-cirrhotic patients regarding HOTTIP at the cut-off value of 13.4, with sensitivity of 32.0% and specificity of 100.0% with areas under curve (AUC) of 53.9 (p value = 0.640, 95% confidence interval C.I 37.1%-70.8%) and accuracy of 66.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Many lncRNAs are identified in various types of cancers, and their dysregulated expression is correlated with tumor progression and patients’ survival, thus making them promising markers for the diagnosis and prognosis. For example, the lncRNAs TUG1 [ 36 ], UCA1 [ 37 ], SPRY4-IT1 [ 38 ], HULC [ 9 ], HOTTIP [ 39 ], H19 [ 40 ] and HOTAIR [ 41 ] were found to be novel promising biomarkers for poor prognosis in human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Its role in human carcinogenesis was firstly revealed in HCC [ 89 ] and has since been described in colorectal [ 123 , 124 ], gastric [ 125 , 126 , 127 ], pancreatic [ 128 , 129 ], and lung cancers [ 130 ], as well as in osteosarcoma [ 131 ] and glioma [ 132 ]. The results from these studies were collectively analyzed in three parallel meta-analyses, all of which clearly showed that the high expression of HOTTIP correlates with shorter overall survival, higher tumor grade and poor prognosis [ 133 , 134 , 135 ].…”
Section: Widespread Lncrna Dysregulation In Hccmentioning
confidence: 99%